2020
DOI: 10.1093/pcp/pcaa058
|View full text |Cite
|
Sign up to set email alerts
|

Symplasmic Isolation Contributes to Somatic Embryo Induction and Development in the Tree Fern Cyathea delgadii Sternb

Abstract: In this report, we describe studies on symplasmic communication and cellular rearrangement during direct somatic embryogenesis (SE) in the tree fern Cyathea delgadii. We analyzed changes in the symplasmic transport of low-molecular weight fluorochromes, such as 8-hydroxypyrene-1,3,6-trisulfonic acid, trisodium salt (HPTS) and fluorescein (delivered to cells as fluorescein diacetate – FDA), within stipe explants and somatic embryos originating from single epidermal cells and developing during 16 days long cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…is system can easily track it from the induction phase through the first embryogenic division to the formation of embryo segments from which organs differentiate. Current research has shown that the course of SE in C. delgadii depends on cytoplasmic connectivity between the cells of the initial explant and the cells of the somatic embryo (Grzyb et al, 2020). ese studies also confirmed the occurrence of isolation during the induction of embryogenesis and differentiation of the embryo body.…”
Section: Intercellular Communicationmentioning
confidence: 73%
“…is system can easily track it from the induction phase through the first embryogenic division to the formation of embryo segments from which organs differentiate. Current research has shown that the course of SE in C. delgadii depends on cytoplasmic connectivity between the cells of the initial explant and the cells of the somatic embryo (Grzyb et al, 2020). ese studies also confirmed the occurrence of isolation during the induction of embryogenesis and differentiation of the embryo body.…”
Section: Intercellular Communicationmentioning
confidence: 73%
“…Symplasmic domains were determined for embryogenesis [ 66 , 81 , 82 , 83 , 84 ], androgenesis [ 85 ], and somatic embryogenesis [ 67 , 86 , 87 , 88 , 89 , 90 ].…”
Section: Symplasmic Isolation As a Mechanism Controlling Somatic Embr...mentioning
confidence: 99%
“…Studies on symplasmic communication during SE were performed using the example of direct somatic embryogenesis in the tree fern Cyathea delgadii [ 87 ]. An analysis using low-molecular-weight fluorochromes showed that the restriction in symplasmic communication preceded the induction of SE.…”
Section: Symplasmic Isolation As a Mechanism Controlling Somatic Embr...mentioning
confidence: 99%
“…Badania komunikacji symplastowej w trakcie somatycznej embriogenezy na przykładzie Arabidopsis wykazały, ze izolacja symplastowa jest niezbędnym czynnikiem dla przejścia komórek ze stanu somatycznego w embriogenny [41,50]. Podobną zasadę wykazano w trakcie somatycznej embriogenezy paproci drzewiastej Cyathea delgadii Sternb [51].…”
Section: Embriogenezaunclassified